Evaluation of thyroid nodules by ultrasonography with cytological and histopathological correlation - Asish Mandal,; Sundara Raja Perumal R,; Debasish Nandi, (Asian Journal of Medical Sciences, 2023)
Background: Nodular thyroid is a common clinical entity. The optimum diagnostic strategy for the patient with nodular thyroid is still a matter of debate. A thyroid nodule is a well-defined discrete lesion, sonographically distinct from the surrounding thyroid parenchyma. Thyroid nodules occur with relatively high frequency in the general population with prevalence of 4–7% by palpation alone, 13%–67% by sonographic evaluation, and 50% at autopsy. It is estimated that 4–8% of adult women and 1–2% of adult men have thyroid nodules that can be felt on clinical examination. However, in contrast to high prevalence of thyroid nodules, the prevalence of thyroid malignancy is low. <7% of thyroid nodules are malignant. Aims and Objectives: The present study was undertaken to evaluate the diagnostic efficacy of ultrasonography (USG) and color Doppler in differentiating benign and malignant thyroid nodules and in comparing the findings with results of fine needle aspiration cytology (FNAC). Materials and Methods: A prospective study was carried out on 65 patients from 11–80 years age group of both sexes, presenting with thyroid nodules. All patients were evaluated by gray scale USG and color Doppler and then subjected to FNAC. Histopathology was done whenever required. The results of FNAC were compared with that of USG and color Doppler. Results: The majority of the cases presented were females between the age group of 21–50 years. Swelling in the anterior neck was the presenting complaint in all 65 cases (100%). The most of thyroid nodules were benign in nature. The sensitivity and specificity of US in diagnosing malignant lesions were 80% and 86%, respectively. The most common presentation was from the females in the age group of 21–50 years, with swelling in the anterior neck. Conclusion: USG with color Doppler is a safe, reliable, and cost-effective diagnostic modality with a high sensitivity and specificity and is the single best radiological investigation for non-invasive evaluation of thyroid nodules. However, a combination of FNAC and USG gives optimum results and can avoid unnecessary surgery.